Implementasi Pendidikan Karakter Menurut Perspektif Thomas Lickona Ditinjau dari Peran Pendidik PAK - Glorya Loloagin; Djoys Anneke Rantung; Lamhot Naibaho (Journal on Education, 2023)
Educators have an important role in helping the success of education in schools. Educators have a great responsibility in producing quality students who also have good and moral character. In education, educators do not only act as teachers but educators must also be good examples and role models for the development of students in schools. According to Lickona there are seven reasons why character education must be delivered. The seven origins referred to are as follows. 1). The best way to ensure children (students) have a good personality in life. 2). Ways to improve academic achievement. 3). Some students cannot form a strong character for themselves elsewhere. 4). Preparing students to respect other parties or people and be able to live in a diverse society. 5). Departing from the root of the problem related to social-moral problems, such as impoliteness, dishonesty, violence, violations of sexual activity, and low work (learning) ethic. 6). Best preparation for behavior in the workplace. And 7). Learning cultural values which are part of civilized work.